2012
DOI: 10.1007/s10120-012-0226-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequent microsatellite instability in papillary and solid-type, poorly differentiated adenocarcinomas of the stomach

Abstract: Background Microsatellite instability (MSI) has been observed in 8-39 % of sporadic gastric cancers. However, despite numerous reports indicating a significant relationship between intestinal-type histology and MSI, detailed correlation between histological subtypes and MSI remains obscure. The purpose of the present study is to clarify the relationship between histological subtype and microsatellite status in gastric carcinomas. Methods Microsatellite status was examined for 464 consecutive gastric carcinomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
46
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 23 publications
7
46
1
Order By: Relevance
“…Many other publications linked MSI to the intestinal type15,16,25,32,35 and could not show MSI in poorly cohesive carcinomas. Another study performed in Japan40 did not find an association with the tumor phenotype.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many other publications linked MSI to the intestinal type15,16,25,32,35 and could not show MSI in poorly cohesive carcinomas. Another study performed in Japan40 did not find an association with the tumor phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…Only 2 groups previously used our 5 markers 24,37. Others used only 1 or 2 markers15,29,36,40 mixed microsatellite markers established for colon cancer with other microsatellite markers, or even used a panel of 40 different markers33 (Table 2). Different marker panels probably lead to different test results.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite-instable gastric adenocarcinomas have been recognized previously as a distinct group based on clinicopathologic 37 and molecular findings. 6,38 However, aberrant E-cadherin or p53 expression may be seen in this subgroup, with hypermethylation of CDH1 27 and abnormalities in TP53 (most frequently as a result of loss of heterozygosity).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that most MSI-high tumors are of the intestinal histotype, located in the distal portion of the stomach, and occur more frequently in older women [27]. In particular, MSI-high tumors show distinct histological features, such as mucinous, serrated, and medullary patterns, in advanced cancers [27].…”
Section: Discussionmentioning
confidence: 99%